2019
DOI: 10.1016/j.eurox.2019.100026
|View full text |Cite
|
Sign up to set email alerts
|

Stillbirth and associated perinatal outcomes in obstetric cholestasis: a systematic review and meta-analysis of observational studies

Abstract: Background Obstetric cholestasis is a condition occurring in pregnancy with suspected adverse perinatal outcomes. Stillbirth is a significant adverse event associated with obstetric cholestasis and considered for intervention in pregnancy. Objectives There are multiple studies with epidemiological data with regards to the outcomes of obstetric cholestasis. Our hypothesis is to the test the association of stillbirth and related outcomes in obstetric cholestasis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 50 publications
0
8
1
Order By: Relevance
“…Mohan et al reported that induction of labor resulted in high cesarean section rates, but in our study, 54.6% of patients who were induced with E2 and/or E1 had a normal vaginal delivery. 24 In this study, 31 (48.4%) women had FTVD contrary to a study by Geenes and Williamson who showed that preterm deliveries were significantly associated with ICP. 13 Another study by Kong et al stated 21% of ICP occurred as premature deliveries.…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…Mohan et al reported that induction of labor resulted in high cesarean section rates, but in our study, 54.6% of patients who were induced with E2 and/or E1 had a normal vaginal delivery. 24 In this study, 31 (48.4%) women had FTVD contrary to a study by Geenes and Williamson who showed that preterm deliveries were significantly associated with ICP. 13 Another study by Kong et al stated 21% of ICP occurred as premature deliveries.…”
Section: Discussioncontrasting
confidence: 78%
“…20 Literature reports that postpartum hemorrhage is 2.33 times more common in pregnancies complicated by ICP as compared to pregnancies not complicated by ICP. 24 Another study in France showed 20.7% of pregnant women with ICP had PPH. Our study shows one woman (1.5%) to have PPH, contrary to the above studies (p = 0.032 b ).…”
Section: Discussionmentioning
confidence: 99%
“…After screening abstracts, 266 full‐text papers were retrieved for review, of which 197 were excluded (Figure 1, Table S1a). Sixty‐nine systematic reviews were included 3,9,17,23–88 …”
Section: Resultsmentioning
confidence: 99%
“…A systematic review and individual patient data meta-analysis published in 2019 examined epidemiological studies for the association of stillbirth and associated outcomes in relation to obstetric cholestasis. Its findings were that obstetric cholestasis is associated with increased rates of both iatrogenic and spontaneous preterm births, meconium-stained amniotic fluid, neonatal unit admission and increased risk of stillbirth only when peak serum bile acid concentrations were 100 µmol/L or higher, therefore challenging the previous widely held belief that obstetric cholestasis is associated with increased stillbirth rates across all bile acid concentrations 3…”
Section: Introductionmentioning
confidence: 90%